Changing the equation: Leveraging true cost accounting to accelerate agri-food systems transformation - Klaus, Lisa Maria; Riemer, Olivia; Müller, Alexander; Zhang, Wei (Think Tank for Sustainability, 2024)
The global agri-food system, from field to fork, is failing to nourish billions of people properly, is responsible for nearly a third of all greenhouse gas emissions and is a major driver of biodiversity loss. As it currently operates, this system imposes significant hidden costs on the environment, on the workers who produce ‘cheap’ food in dangerous or precarious conditions, consumers, and society as a whole. These hidden costs, or ‘externalities’, include water pollution remediation, social support for underpaid workers, and public health costs related to diet-related diseases, none of which are captured by traditional economic metrics. Externalities are prevalent in all sectors of the economy, not just agri-food systems, and are systematically ignored in conventional accounting and reporting systems. This omission leads to distorted market signals that encourage unsustainable business practices, the consequences of which are borne by society, particularly disadvantaged communities, and will weigh heavily on future generations while the polluters reap financial rewards. Addressing externalities is therefore essential to building an economic system that supports sustainable development.